Institutional arbitration versus ad hoc arbitration: Chinese and Iranian perspectives - MAZIYAR SHOKRANI (Journal of Advanced Research in Social Sciences and Humanities, 2018)
Aim: There are merits and drawbacks to both institutional arbitration and ad hoc arbitration. In contrast to institutional arbitration, which occurs within the framework of an arbitral organisation, ad hoc arbitration, which is not administered by any institution, requires the parties to make their own arrangements for selecting the arbitrators and designating applicable laws and rules of procedure. The point of this piece is to contrast the effectiveness of these forms of arbitration under two distinct legal regimes.Method: This research will utilise a doctrinal review and a comparative test to examine the two legal systems.Findings: Institutional arbitration has not been formally introduced into Iran’s legal system, and ad hoc arbitral awards are not recognised in China. It is recommended in this paper that Iran adopt institutional arbitration because of its many benefits and that China recognises ad hoc arbitration to honour the autonomy of the parties involved.Implications/Novel Contribution: The research fills a gap in the existing literature by providing an in-depth analysis of the legal systems in both countries. In both countries, credit is given differently.